Overconfidence bias and investment performance: A mediating effect of risk propensity - Syed Zain ul Abdin; Fiza Qureshi; Jawad Iqbal; Sayema Sultana (Borsa İstanbul Review, 2022)
This study examines the determinants of overconfidence bias that, in turn, influence investment performance via risk propensity. This study also investigates the three cognitive biases that lead to overconfidence bias, influence investment performance, and establish the indirect relationship through risk propensity. The mixed methodology is applied to examine the proposed research model. The results depict that all the cognitive biases influence the risk propensity and investment performance via risk propensity. The illusion of control is the strongest predictor of risk propensity and investment performance. Furthermore, findings imply that all the cognitive biases have a positive relation with investment performance. This study provides policy implications to practitioners and individual investors.
Keywords: 330; Illusion of control; Individual investors; Investment performance; Optimism; Overconfidence bias; Self-attribution